It's Complicated: Intraroot System Variability of Respiration and Morphological Traits in Four Deciduous Tree Species . Issue 2 (19th June 2014) - Rewald, Boris; Rechenmacher, Andreas; Godbold, Douglas L.
Abstract : Extended branching order classification describes morphological variability in root systems and respiration better than traditional root diameter classes or root orders alone . Abstract: Within branched root systems, a distinct heterogeneity of traits exists. Knowledge about the ecophysiology of different root types is critical to understand root system functioning. Classification schemes have to match functional root types as closely as possible to be used for sampling and modeling. Among ecophysiological root traits, respiration is of particular importance, consuming a great amount of carbon allocated. Root architecture differs between the four deciduous tree seedlings. However, two types of terminal root segments (i.e. first and second orders), white colored and brown colored, can be distinguished in all four species but vary in frequency, their morphology differing widely from each other and higher coarse root orders. Root respiration is related to diameter and tissue density. The use of extended root ordering (i.e. order and color) explains the variance of respiration two times as well as root diameter or root order classes alone. White terminal roots respire significantly more than brown ones; both possess respiration rates that are greater than those of higher orders in regard to dry weight and lower in regard to surface area. The correlation of root tissue density to respiration will allow us to use this continuous parameter (or easier to determine dry matter content) to model the respiration within woody root systems without having to determine nitrogen contents. In addition, this study evidenced that extended root orders are better suited than root diameter classes to picture the differences between root functional types. Together with information on root order class frequencies, these data allow us to calculate realistic, species-specific respiration rates of root branches.